Data acquisition system (DAS) and real time computing for energy management in building: power data consideration / Mohd Hamdan Hamzah - Hamzah, Mohd Hamdan (1994)
This project describes the basic design features and operation of a Data Acquisition System (DAS) that is intended for use in energy management of buildings. It also describes how the software is developed in conjunction with the DAS. A high level language i.e. Turbo Pascal Version.6 is used. The software is then simulated to the real world condition whereby the energy parameters that are monitored are currently being displayed on the computer screen at some interval time. The signals that are obtained at each of the monitored points are conditioned, so that it can be handled by the interface card and can be used by personal computer. Protection circuit using crowbar overvoltage and overcurrent was introduced before the interface card for protection and isolation.